ARCHIMED: A Network of Integrated Information Systems - Thurler, G.; Borst, F.; Bréant, C.; Campi, D.; Jenc, J.; Lehner-Godinho, B.; Maricot, P.; Scherrer, J. R. (Methods of Information in Medicine, 2000)
ARCHIMED is a Network of Integrated Information Systems (NIIS). This novel concept of hospital information system has a major advantage over the currently used distributed systems. The normalized representation structure of its databases enable its Navigators to reach simultaneously not only the data coming from different hospital departments, laboratories, and other hospital facilities, but also the data from different hospitals associated in the network.
Keywords: Network Information System; Integrated Information System; Medical Application